In Vivo Activity of the Benzothiazinones PBTZ169 and BTZ043 against Nocardia brasiliensis - González-Martínez, Norma Alejandra; Lozano-Garza, Hector Gerardo; Castro-Garza, Jorge; De Osio-Cortez, Alexandra; Vargas-Villarreal, Javier; Cavazos-Rocha, Norma; Ocampo-Candiani, Jorge; Makarov, Vadim; Cole, Stewart T.; Vera-Cabrera, Lucio (PLOS Neglected Tropical Diseases, 2015)
Background Mycetoma is a neglected, chronic, and deforming infectious disease caused by fungi and actinomycetes. In Mexico, N. brasiliensis is the predominant etiologic agent. Therapeutic alternatives are necessary because the current drug regimens have several disadvantages. Benzothiazinones (BTZ) are a new class of candidate drugs that inhibit decaprenyl-phosphoribose-epimerase (DprE1), an essential enzyme involved in the cell wall biosynthesis of Corynebacterineae. Methodology/Principal findings In this study, the in vitro activity of the next generation BTZ, PBTZ169, was tested against thirty Nocardia brasiliensis isolates. The MIC50 and MIC90 values for PBTZ169 were 0.0075 and 0.03 μg/mL, respectively. Because Nocardia is a potential intracellular bacterium, a THP-1 macrophage monolayer was infected with N. brasiliensis HUJEG-1 and then treated with PBTZ169, resulting in a decrease in the number of colony-forming units (CFUs) at a concentration of 0.25X the in vitro value. The in vivo activity was evaluated after infecting female BALB/c mice in the right hind food-pad. After 6 weeks, treatment was initiated with PBTZ169 and its activity was compared with the first generation compound, BTZ043. Both BTZ compounds were administered at 100 mg/kg twice daily by gavage, and sulfamethoxazole/trimethoprim (SXT), at 100 mg/kg sulfamethoxazole, was used as a positive control. After 22 weeks of therapy, only PBTZ169 and SXT displayed statistically significant activity. Conclusion These results indicate that DprE1 inhibitors may be useful for treating infections of Nocardia and may therefore be active against other actinomycetoma agents. We must test combinations of these compounds with other antimicrobial agents, such as linezolid, tedizolid or SXT, that have good to excellent in vivo activity, as well as new DprE1 inhibitors that can achieve higher plasma levels.